\(\mathcal{I}\)-STATISTICAL CONVERGENCE OF COMPLEX UNCERTAIN SEQUENCES IN MEASURE - Amit Halder; Shyamal Debnath (Ural Mathematical Journal, 2024)
The main aim of this paper is to present and explore some of properties of the concept of \(\mathcal{I}\)-statistical convergence in measure of complex uncertain sequences. Furthermore, we introduce the concept of \(\mathcal{I}\)-statistical Cauchy sequence in measure and study the relationships between different types of convergencies. We observe that, in complex uncertain space, every \(\mathcal{I}\)-statistically convergent sequence in measure is \(\mathcal{I}\)-statistically Cauchy sequence in measure, but the converse is not necessarily true.